Rice residue recirculation enhances mobilization and plant acquisition of soil inorganic phosphorus by increasing silicon availability in a semi-arid Inceptisol - Ghosh, Avijit; Biswas, Dipak Ranjan; Bhattacharyya, Ranjan; Das, Shrila; Das, Tapas K.; Lal, K.; Saha, Supradip; Alam, Khurshid; Casini, Ryan; Elansary, Hosam O.; Manjangouda, S. S. (Frontiers in Sustainable Food Systems, 2023)
Massive amounts of rice straw (RS) provide a significant problem for in situ and instant management at a low cost. On the other hand, mobilizing soil phosphorus (P) from inorganically fixed pools may increase its effectiveness over time. To address both of these issues at once as well as to decide the optimum rate of RS for P mobilization, this study was carried out to determine whether the use of RS + P solubilizing microbes (PSMs) could solubilize a sizable portion of the soil's fixed P and affect P transformation, silicon (Si) concentration, organic acid (OA) concentration, and enzyme activity to increase wheat yield. Depending on the soil temperature, the application of RS (at 12 Mg ha−1) + PSM could solubilize 3.40–3.66% of the inorganic P. Over control, it minimized the hysteresis impact by 6–8%. The soils of wheat included the acids oxalic acid, citric acid, formic acid, malic acid, and tartaric acid. At maturity stage of wheat, application of RS (at 12 Mg ha−1) + PSM + 75%P raised the activity of dehydrogenase, alkaline phosphatase activity, cellulase, and peroxidase by 1.77, 1.65, 1.87, and 1.82 times above control in soil, respectively. It also boosted Si concentration in the soil increased by 58% over control. Wheat grain yield was 40 and 18% higher under RS (at 12 Mg ha−1) + PSM + 75%P application than under control and 100% P application. Additionally, it increased root volume, length, and P uptake by 2.38, 1.74, and 1.62 times above control, respectively. According to path analysis, P solubilisation by Si and OAs considerably increased P availability in the wheat root zone. Therefore, cultivators could be advised to use RS (at 12 Mg ha−1) + PSM + 75% P of mineral P fertilizer to save 25% P fertilizer without reducing yield.